A bipolar electrode for electrolytic synthesis of succinic acid with high corrosion resistance of heat exchanger
By designing a multipole electrode used in the electrolysis of succinic acid, the electrode exchanges heat through cooling water, and adjusts the electrolyte temperature and electrode surface temperature, the problem of poor corrosion resistance of existing anode materials is solved, and the electrode life is extended and the production cost is reduced.
Patent Information
- Application Number
- CN202011521505.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-21
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-12-21
AI Technical Summary
The existing anode materials for industrial electrolytic synthesis of succinic acid, especially lead alloys and iridium titanium oxide coated electrodes, have problems such as poor corrosion resistance, short service life and high cost. At the same time, it is difficult to select heat exchangers, which affects production stability and cost.
A multipole electrode with high corrosion resistance performance of heat exchangers is designed. By setting a closed cavity in the electrode and heat exchange with cooling water, the electrolyte temperature and electrode surface temperature are regulated, thereby improving the corrosion resistance of the electrode.
It significantly improves the corrosion resistance of the electrode, extends the service life of the electrode, reduces maintenance costs, and solves the problem of difficult heat exchanger material selection. It is suitable for large-scale industrial electrolytic synthesis of succinic acid production.
Smart Images

Figure CN112575342B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrode materials, and relates to an electrode material for large-scale industrial production of succinic acid, and in particular to a bipolar electrode for electrolytic synthesis of succinic acid with high corrosion resistance of a heat exchanger. Background Art
[0002] Succinic acid, commonly known as succinic acid, is an important synthetic intermediate for synthetic medicine and fine chemicals. It is widely used in synthetic plastics, rubber, medicine, protective coatings and other industries. Succinic acid has most of the typical reactions of dibasic acids, such as halogenation, dehydration, esterification, polycondensation, iodination, acylation, oxidation, reduction, etc. A series of monoesters and diesters can be prepared using succinic acid as a substrate. For example, succinic acid is esterified with starch, cellulose and polyols; succinic acid and 1,4-butanediol can undergo polycondensation to synthesize polybutylene succinate (PBS), which is a biodegradable plastic with a very broad market promotion prospect. In recent years, with the implementation of the national plastic ban, the domestic market for succinic acid is expected to exceed an annual output of more than 200,000. Therefore, expanding the scale of production is an inevitable requirement for the rapid development of the current succinic acid market.
[0003] The main methods for industrial preparation of succinic acid include catalytic hydrogenation reduction of maleic acid (ester), biochemical method and electrolytic reduction method. Among them, the catalytic hydrogenation method requires maleic acid ester as raw material, the product is complex and the conversion rate is low; the biochemical method has been widely studied, but the amount of wastewater in the biochemical process is large, and the product contains a variety of monoacids, which cannot be used for the polymerization reaction of PBS; the electrolytic method is widely used by domestic and foreign manufacturers and is currently the main method for the production of succinic acid at home and abroad.
[0004] The electrolytic synthesis of succinic acid uses maleic anhydride as raw material and adopts diaphragm-free electrolysis to synthesize succinic acid. The anode material of the electrolysis device is an iridium-titanium precious metal coated electrode, such as Shandong Feiyang Chemical Co., Ltd. and Shanxi Jinhui Zhaolong Co., Ltd.; or a lead alloy electrode is used, such as Anqing Hexing Chemical Co., Ltd. and Anhui Sanxin Chemical Co., Ltd. The lead alloy anode material has severe electrode corrosion during the electrolysis process, a short life (3-6 months), high maintenance cost of the electrolytic cell, and poor product quality; the iridium-titanium coated electrode is an electrocatalytic oxygen evolution electrode with very good oxygen evolution activity and a large working current, but the electrode is expensive, with a total price of more than 10,000 yuan per square meter of coating and titanium mesh substrate. When the electrolyte temperature rises to 80°C, the electrode life drops sharply, and the electrode life generally does not exceed 3 years. Therefore, the corrosion resistance of the anode material for the industrial electrolytic synthesis of succinic acid has become a key technology for the large-scale production of succinic acid.
[0005] There is heat release during the electrolysis process of electrolytic synthesis of succinic acid. As the electrolysis proceeds, the electrolyte temperature gradually increases, and can even rise to 100°C. In the hot solution, the corrosion resistance of the lead alloy anode and the iridium-titanium coated electrode decreases rapidly. At present, the electrolyte temperature is controlled by an external or internal heat exchanger, but there are problems such as difficulty in selecting materials for the heat exchanger, inconvenience in use, and low heat exchange efficiency. The present invention designs a bipolar electrode that passes cooling water. Through heat exchange between the electrode and the electrolyte, the electrode is cooled to improve the corrosion resistance of the electrode while also acting as a heat exchanger, thereby regulating the electrolyte temperature. Summary of the invention
[0006] The anode materials for electrolytic synthesis of succinic acid in industry generally adopt lead alloy electrodes or iridium titanium oxide coating electrodes, both of which have the disadvantages of poor corrosion resistance and short service life; especially when the electrolyte temperature exceeds 60°C, the corrosion rate increases significantly, thereby affecting the cost and production stability of industrial electrolytic synthesis of succinic acid. The main purpose of the present invention is to solve the problems of easy corrosion, short service life and high cost of the existing insoluble anode lead alloy materials and iridium titanium oxide coating electrodes for industrial electrolytic synthesis of succinic acid, as well as practical problems such as difficulty in selecting materials for heat exchangers, and to provide a self-cooling bipolar electrode for industrial electrolytic production of succinic acid, the bipolar electrode has high corrosion resistance and the characteristics of a heat exchanger, and is particularly suitable for the production of electrolytic synthesis of succinic acid on a large scale of 10,000 tons or more.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] A bipolar electrode for electrolytic synthesis of succinic acid having high corrosion resistance of a heat exchanger, wherein the bipolar electrode is a rectangular parallelepiped with a closed cavity, the front side of the rectangular parallelepiped is an anode side, the back side is a cathode side, and the top side of the rectangular parallelepiped is provided with a cooling water inlet pipe and a cooling water outlet pipe connected to the cavity, external cooling water is input into the cavity through the cooling water inlet pipe and discharged from the cooling water outlet pipe, and the cooling water input into the cavity is used to exchange heat with the electrolyte in contact with the bipolar electrode and regulate the temperature of the electrolyte, and at the same time, the cooling water in the cavity can reduce the temperature of the anode side and the cathode side on the bipolar electrode, thereby significantly improving the corrosion resistance of the electrode.
[0009] Preferably, the material of the bipolar electrode is a metal lead alloy.
[0010] Preferably, the material of the bipolar electrode is metallic titanium, the anode surface is a titanium plate with an IrO2-Ta2O5 coating, and the cathode surface is a titanium plate; more preferably, the material of the bipolar electrode is metallic titanium, a titanium mesh with an IrO2-Ta2O5 coating is welded to the outside of the titanium plate on the anode surface, and the cathode surface is a titanium plate; more preferably, the material of the bipolar electrode is metallic titanium, a titanium mesh with an IrO2-Ta2O5 coating is welded to the outside of the titanium plate on the anode surface, and a titanium mesh is welded to the outside of the titanium plate on the cathode surface.
[0011] Preferably, the cooling water inlet pipe passes through one end of the top surface of the cuboid and extends into the bottom of the cavity, the cooling water outlet pipe is arranged at the other end of the top surface of the cuboid, and the cooling water inlet pipe and the cooling water outlet pipe are connected to the cooling water system outside the electrolytic cell.
[0012] Preferably, two side surfaces of the cuboid are welded with card edges, and the card edges are made of titanium or lead alloy. More preferably, the card edges are strip-shaped protrusions, and the bipolar electrode is inserted into the frame of the plastic electrolytic cell through the card edges; the bottom surface of the bipolar electrode is tightly fitted with the bottom surface of the frame of the electrolytic cell (PP material), dividing the electrolytic cell into different unit electrolytic cells, and the number of unit electrolytic cells is 2-100.
[0013] Preferably, the surface temperature of the bipolar electrode and the temperature of the electrolyte are regulated by controlling the temperature and flow rate of the cooling water introduced into the bipolar electrode.
[0014] Preferably, any one of the above-mentioned electrolytic synthesis of succinic acid bipolar electrodes with high corrosion resistance of the heat exchanger is suitable for large-scale industrial electrolytic synthesis of succinic acid production, and the applicable current density of the bipolar electrode is 100-1000A / m 2 .
[0015] The bipolar electrode of the present invention is applied to the industrial electrolytic synthesis of succinic acid. Compared with the prior art, the main beneficial effects are as follows: (1) in a 10wt%+(1-15)wt% sulfuric acid succinic acid electrolyte, the electrolytic reaction is carried out at 500A / m 2 At a current density of 500A / m, the anode material uses a lead alloy electrode, and the service life is increased from 6 months to 1 year; (2) in a 10wt% + 1-15wt% succinic acid sulfuric acid electrolyte, 2 Under the current density of 1.5 ℃, the anode material uses iridium-titanium coated electrode, and its service life is increased from the original 30 months to 48 months; (3) It solves the problem of difficult material selection for industrial electrolytic synthesis of succinic acid heat exchangers, reduces the corrosion of titanium heat exchangers, and can control the electrode surface temperature below 50℃ and the electrolyte temperature to 85℃, thereby increasing the temperature range of the electrolyte and making it suitable for large-scale industrial electrolytic synthesis of succinic acid production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic diagram of a bipolar electrode for electrolytic synthesis of succinic acid having high corrosion resistance of a heat exchanger;
[0017] Figure 1 In the figure, 1- bipolar electrode, 2- anode surface, 3- cathode surface, 4- clamp edge, 5- cooling water inlet pipe, 6- cooling water outlet pipe, 7- titanium mesh, 8- IrO2-Ta2O5 coating / titanium mesh.
[0018] Figure 2It is a schematic diagram of electrolysis experiment;
[0019] Figure 2 In the figure, 9-side plate is connected to the positive pole of the power supply, 10-side plate is connected to the negative pole of the power supply, 11-external cooling water inlet pipe, 12-external cooling water outlet pipe.
[0020] Figure 3 1 is a graph showing the voltage variation of different bipolar electrode enhanced life tests in Example 1;
[0021] Figure 4 This is a graph showing the voltage changes in different bipolar electrode experiments without cooling water in Example 2. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0023] Example 1
[0024] Reference Figure 1 Schematic diagram of processing a small experimental bipolar electrode 1, the bipolar electrode 1 is a cuboid with a closed cavity, the front of the cuboid is an anode surface 2, the back is a cathode surface 3, the top surface of the cuboid is provided with a cooling water inlet pipe 5 and a cooling water outlet pipe 6, the cooling water inlet pipe 5 passes through one end of the top surface of the cuboid and extends into the bottom of the cavity, the cooling water outlet pipe 6 is provided at the other end of the top surface of the cuboid, the cooling water inlet pipe 5 and the cooling water outlet pipe 6 are connected to the cooling water system outside the electrolytic cell, the external cooling water is input into the cavity through the cooling water inlet pipe and discharged from the cooling water outlet pipe, the cooling water input into the cavity is used to exchange heat with the electrolyte in contact with the bipolar electrode, and the temperature of the electrolyte is regulated, and at the same time, the cooling water in the cavity can cool the anode surface and the cathode surface on the bipolar electrode, significantly improving the corrosion resistance of the bipolar electrode; the two side surfaces of the bipolar electrode 1 are the two side surfaces of the cuboid It is welded with a card edge 4; the material of the bipolar electrode 1 is a metal lead alloy or metal titanium. When the material of the bipolar electrode 1 is metal titanium, the anode surface of the bipolar electrode 1 is a titanium plate provided with an IrO2-Ta2O5 coating, or a titanium plate welded with an IrO2-Ta2O5 coating / titanium mesh 8, and the IrO2-Ta2O5 coating / titanium mesh 8 refers to a titanium mesh provided with an IrO2-Ta2O5 coating; the cathode surface of the bipolar electrode 1 is a titanium plate, or a titanium plate welded with a titanium mesh 7; the titanium plate refers to the corresponding electrode surface formed when the material of the bipolar electrode 1 is metal titanium; the bipolar electrode rectangular parallelepiped length (L) * height (H) * thickness (W) specifications are 40mm (L) * 20mm (H) * 8mm (W), the card edge specification is 4mm, the cooling water inlet pipe specification is Ф5mm, and the titanium mesh specification is 40mm * 20mm * 1mm. The electrode specifications for the strengthening experiment are as follows:
[0025] Table 1 Bipolar electrodes used in the experiment
[0026]
[0027] The above electrodes were subjected to enhanced life tests to evaluate the corrosion resistance of the electrodes. The electrolyte was 10wt% H2SO4 + 5wt% succinic acid solution, and the electrolytic cell was divided into a 5-pole 4-chamber electrolytic device using four types of bipolar electrodes AD, as shown in the attached Figure 2 As shown, 9 is the side plate connected to the positive pole of the power supply, 10 is the side plate connected to the negative pole of the power supply, 11 is the external cooling water inlet pipe, 12 is the external cooling water outlet pipe, the bipolar electrode spacing is 1cm, and the actual test area of the electrode is 6cm 2 , constant current density 12A (current density 20000A / m 2 ) electrolysis, turn on the cooling water system, adjust the cooling water flow rate to control the electrolyte temperature at 55±1℃, record the change of the cell voltage over time, and a sharp increase in the cell voltage is considered to be anode failure, and record the electrolysis time. After the electrode fails, wash it and dry it at 120℃. Weigh the mass of the three middle bipolar electrodes and record the average weight loss of the electrodes before and after electrolysis strengthening. Electrodes A, B, C, and D are electrolyzed for 120h, and the deposited lead mud needs to be removed from electrode A. The cumulative weight losses are 36.02g, 0.564g, 0.64g, and 0.54g, respectively. The results of the change in electrolysis voltage are shown in the figure. Figure 3 .
[0028] Figure 3 The results show that the life of the D electrode in the strengthening experiment is up to 130h. The plate life of the titanium-based bipolar electrode plate-shaped coating electrode is lower than that of the mesh electrode. The use of mesh electrodes as cathodes is conducive to reducing current density and improving electrode life. The weight loss of the three titanium-based electrodes B, C, and D is not obvious, which may be related to the fact that titanium dioxide is generated while the titanium substrate surface coating falls off and increases the mass of the electrode. The test results of the lead alloy A electrode show that the cell voltage increases slowly, and the electrode corrosion weight loss is serious. After 120h, the weight loss reaches 39.04%.
[0029] Example 2
[0030] According to the method of Example 1, four bipolar electrodes A, B, C, and D were used as research objects. No cooling water was passed, and the temperature of the electrolysis was naturally increased. The electrolyte lost due to evaporation was added in time. After 2 hours of electrolysis, the temperature rose to 90-95°C. The voltage-time relationship of the electrolysis was tested, the enhanced service life of the electrode was tested, and the corrosion resistance of the electrolysis was evaluated. The results are as follows: Figure 4 .
[0031] Figure 4The results show that the temperature of the electrolyte rises naturally without cooling water, and the electrolyte temperature reaches 90-95℃, which significantly reduces the electrode life. The average cell voltage of the D electrode exceeds 4.5V after 70h, and then the electrode coating is rapidly damaged and the cell voltage rises sharply. The lead alloy is severely corroded, and the electrode weight loss is 52.3% after 70h of electrolysis.
[0032] Embodiment 3-7
[0033] According to the method of Example 1, a D bipolar electrode was used as the research object, the cooling water temperature and flow rate were controlled, and the electrolyte temperature was controlled to be 40°C, 50°C, 60°C, 70°C and 80°C respectively for enhanced life test, and the electrolyte lost due to evaporation was added in time. When the unit cell voltage increased to 25.0V, the electrode was considered to have failed. The test results recorded the cumulative electrolysis time as shown in Table 2.
[0034] Table 2 Regulating the electrode enhancement life at different electrolyte temperatures
[0035] Example Example 3 Example 4 Example 5 Example 6 Example 7 Temperature / ℃ 40 50 60 70 80 Time / h 162.8 151.4 146.0 145.5 144.8
[0036] Example 8
[0037] use Figure 1 The device electrolyzes succinic acid. The electrode adopts bipolar electrode D. The electrolyte composition is 8% sulfuric acid + 10% maleic acid (initial concentration of feed). The cooling water flow rate and temperature are controlled. The electrolyte temperature is controlled at 70±2℃. The cathode and anode current densities are both 600A / m 2 (The current value is 3.6A), constant current combined with variable current control electrolysis to a specific time and then end the electrolysis. The electrolyte is crystallized, centrifuged, recrystallized, dried and other processes to obtain the succinic acid product. Five batches of electrolysis were performed, and the results of the last four batches of electrolysis were statistically analyzed. The current efficiency was 92.2% and the conversion rate was 99.6%.
[0038] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solutions described in the claims.
Claims
1. A bipolar electrode for electrolytic synthesis of succinic acid with high corrosion resistance of heat exchanger, characterized in that: The bipolar electrode is a rectangular parallelepiped with a closed cavity, the front side of the rectangular parallelepiped is the anode side, the back side is the cathode side, and the top side of the rectangular parallelepiped is provided with a cooling water inlet pipe and a cooling water outlet pipe connected to the cavity. External cooling water is input into the cavity through the cooling water inlet pipe and discharged from the cooling water outlet pipe. The cooling water input into the cavity is used to exchange heat with the electrolyte in contact with the bipolar electrode and to regulate the temperature of the electrolyte. At the same time, the cooling water in the cavity can reduce the temperature of the anode side and the cathode side on the bipolar electrode, thereby improving the corrosion resistance of the bipolar electrode. The cooling water inlet pipe passes through one end of the top side of the rectangular parallelepiped and extends into the bottom of the cavity. The cooling water outlet pipe is provided at the other end of the top side of the rectangular parallelepiped. The cooling water inlet pipe and the cooling water outlet pipe are connected to the cooling water system outside the electrolytic cell. The material of the bipolar electrode is titanium metal, wherein the anode surface is a titanium plate with an IrO2-Ta2O5 coating, and the cathode surface is a titanium plate; Alternatively, the material of the bipolar electrode is metallic titanium, wherein a titanium mesh with an IrO2-Ta2O5 coating is welded to the outside of the titanium plate on the anode surface, and the cathode surface is a titanium plate.
2. According to claim 1, a bipolar electrode for electrolytic synthesis of succinic acid having high corrosion resistance of a heat exchanger, characterized in that: The material of the bipolar electrode is titanium metal, wherein a titanium mesh with an IrO2-Ta2O5 coating is welded outside the titanium plate on the anode side, and a titanium mesh is welded outside the titanium plate on the cathode side.
3. According to claim 1, a bipolar electrode for electrolytic synthesis of succinic acid having high corrosion resistance of a heat exchanger, characterized in that: The two sides of the cuboid are welded with clamping edges, and the bipolar electrode is inserted into the frame of the electrolytic cell through the clamping edges. The bottom surface of the bipolar electrode is tightly fitted with the bottom surface of the frame of the electrolytic cell. Multiple bipolar electrodes divide the electrolytic cell into 2-100 unit electrolytic cells.
4. According to claim 1, a bipolar electrode for electrolytic synthesis of succinic acid having high corrosion resistance of a heat exchanger, characterized in that: The surface temperature of the bipolar electrode and the temperature of the electrolyte are regulated by controlling the temperature and flow rate of the cooling water introduced into the bipolar electrode.
5. An application of a bipolar electrode for electrolytic synthesis of succinic acid having high corrosion resistance in a heat exchanger according to any one of claims 1 to 4, characterized in that: Applied to large-scale industrial electrolytic synthesis of succinic acid production, the applicable current density of the bipolar electrode is 100-1000A / m 2 .
Citation Information
Patent Citations
Electrolytic synthesis succinic acid bipolar electrode with high corrosion resistance of heat exchanger
CN215799935U